2011
DOI: 10.3390/rs3102110
|View full text |Cite
|
Sign up to set email alerts
|

Using Remote Sensing Products for Environmental Analysis in South America

Abstract: Land cover plays a major role in many biogeochemical models that represent processes and connections with terrestrial systems; hence, it is a key component for public decisions in ecosystems management. The advance of remote sensing technology, combined with the emergence of new operational products, offers alternatives to improve the accuracy of environmental monitoring and analysis. This work uses the GLOBCOVER, the Vegetation Continuous Field (VCF), MODIS Fire Radiative Power (FRP) and the Tropical Rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Additionally, the availability of operational satellite-based products, such as land cover, temperature, rainfall, tree cover, etc., provide prospects for assessing and quantifying the impact of wildfires on the ecosystems and biodiversity. However, only a few studies [12][13][14] have exploited these products for this purpose. Using GLOBCOVER, the Vegetation Continuous Field (VCF), Moderate Resolution Imaging Spectroradiometer (MODIS) Fire Radiative Power (FRP) and the Tropical Rainfall Measuring Mission (TRMM) datasets, Cardozo, Shimabukuro, Pereira and Silva [12] found that biomass of broadleaved evergreen or semi-deciduous forest were mostly burned, attributed to grassland management practices, agricultural land clearing and the deforestation of the Amazon tropical rainforest.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the availability of operational satellite-based products, such as land cover, temperature, rainfall, tree cover, etc., provide prospects for assessing and quantifying the impact of wildfires on the ecosystems and biodiversity. However, only a few studies [12][13][14] have exploited these products for this purpose. Using GLOBCOVER, the Vegetation Continuous Field (VCF), Moderate Resolution Imaging Spectroradiometer (MODIS) Fire Radiative Power (FRP) and the Tropical Rainfall Measuring Mission (TRMM) datasets, Cardozo, Shimabukuro, Pereira and Silva [12] found that biomass of broadleaved evergreen or semi-deciduous forest were mostly burned, attributed to grassland management practices, agricultural land clearing and the deforestation of the Amazon tropical rainforest.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation of native landcover categories by the decision tree resulted in four very broad groups and, consequently, the predictions corresponded more to changes at the biome level than to vegetation classes. This might be a consequence of the Globcover database we used in the model, which does not take topography, an important predictor of vegetation into account [ 61 ]. Despite the generality of our results, they reveal some interesting trends.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible source of uncertainty, for which we had less control, was the initial database of our modeling. A comparison of different digital databases has shown that Globcover data overestimate the closed forest class [ 61 ]. This class occupied the largest part of the original landcover map and the largest predicted area after modeling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effects measured in primary forests, droughts also play a major role on the increase in fire susceptibility in Amazonian forests. It has been estimated that fires in the Amazon increased by 42% from 1998 to 2006 [147], with highest incidence in the arc of deforestation [148]. For instance, the 1997/98 drought affected the savannahs in Roraima, as 53% of the area burned in 1997/1998 in contrast to 1998/1999 (a wet year: 30% burned) and 1999/2000 (a normal year: 36% burned) [139].…”
Section: Drought Effectsmentioning
confidence: 99%